Moving nanostructures: Pulse-induced positioning of supramolecular assemblies - Nickel, Anja; Ohmann, Robin; Meyer, Joerg; Grisolia, Maricarmen; Joachim, Christian; Moresco, Francesca; Cuniberti, Gianaurelio (ACS nano, 2013)
For the development of nanoscale devices, the manipulation of single atoms and molecules by scanning tunneling microscopy is a well-established experimental technique. However, for the construction of larger and higher order structures, it is important to move not only one adsorbate but also several at the same time. Additionally, a major issue in standard manipulation experiments is the strong mechanical interaction of the tip apex and the adsorbate, which can damage the system under investigation. Here, we present a purely electronic excitation method for the controlled movement of a weakly interacting assembly of a few molecules. By applying voltage pulses, this supramolecular nanostructure is moved in a controlled manner without losing its collective integrity. Depending on the polarity and location of the applied voltage, the movement can be driven in predefined directions. Our gentle purely electronic approach for the controlled manipulation of nanostructures opens new ways to construct molecular devices. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: manipulation; scanning tunneling microscopy; spectroscopy; supramolecular structures; voltage pulses